2012
DOI: 10.1016/j.neubiorev.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Creatine metabolism and psychiatric disorders: Does creatine supplementation have therapeutic value?

Abstract: Athletes, body builders, and military personnel use dietary creatine as an ergogenic aid to boost physical performance in sports involving short bursts of high-intensity muscle activity. Lesser known is the essential role creatine, a natural regulator of energy homeostasis, plays in brain function and development. Creatine supplementation has shown promise as a safe, effective, and tolerable adjunct to medication for the treatment of brain-related disorders linked with dysfunctional energy metabolism, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
141
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(148 citation statements)
references
References 269 publications
(369 reference statements)
3
141
0
4
Order By: Relevance
“…For instance, traits like emotional resilience enable some individuals to persevere in tasks such as job search that others may give up on (Moorhouse and Caltabiano, 2007). There is also evidence that creatine is negatively associated with mental disorders such as depression (Allen, 2012). Conversely, depression lowers employment probabilities, though it seems to have no impact on weekly hours worked nor hourly earnings (Peng et al, 2013).…”
Section: Theory and Empirical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, traits like emotional resilience enable some individuals to persevere in tasks such as job search that others may give up on (Moorhouse and Caltabiano, 2007). There is also evidence that creatine is negatively associated with mental disorders such as depression (Allen, 2012). Conversely, depression lowers employment probabilities, though it seems to have no impact on weekly hours worked nor hourly earnings (Peng et al, 2013).…”
Section: Theory and Empirical Evidencementioning
confidence: 99%
“…It could be that creatine has positive effects on cognitive performance particularly in stressful situations. Positive effects of creatine on cognitive behaviour have been found especially in situations associated with reduced brain creatine, such as sleep deprivation, mild exercise and stressful mathematical tasks (Allen, 2012 Turban et al, 2009). Therefore, apart from Extraversion, these results suggest that higher levels of creatine might be associated with better performance in the labour market.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…As a robustness check, we reran all regressions with control variables for meat and fish intake in 1980, because these may be confounding factors in the relation between creatine and entrepreneurship (Allen 2012). These analyses were based on somewhat smaller subsamples because of data availability, but the results (available upon request from the authors) are in line with the findings reported here.…”
Section: Resultsmentioning
confidence: 69%
“…It enhances physical performance, for example in high-intensity exercise (Wyss and Kaddurah-Daouk 2000), and improves mental ability and cognition (Rae et al 2003;Allen 2012). Therefore, greater effort intensity may result in labour market outcomes in which great effort is needed and rewarded as creatine reduces (increases) the costs (returns) to effort.…”
Section: Introductionmentioning
confidence: 99%